2021
DOI: 10.1590/1678-4324-2021200075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type-2 Diabetes Mellitus in Retinopathy Patients on MDA, SOD Activity and its Correlation with HbA1c

Abstract: Diabetic retinopathy (DR) is a metabolic disorder of the retina and one of the common problems of Type-2 diabetes mellitus (T-2DM) causing visual loss even at teen ages. In this research article, oxidative stress was the main cause due to reactive oxygen species (ROS) generation at hyperglycemic state and become as the focus point of this study to describe (DR) complication onset. The present study was conducted to compare three groups: T-2DM with complication, T-2DM without complication and control group. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…This finding agrees with other studies, which showed decreased levels of SOD and CAT in patients with T2D [30]. Hou et al (2021) reported a statistically significant decrease in the SOD activity in participants with T2D when compared with that in healthy individuals [5]. Similarly, Lipa et al (2016) concluded that low serum levels of SOD significantly correlated with the increased risk of T2D and cataract development among individuals with T2D [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding agrees with other studies, which showed decreased levels of SOD and CAT in patients with T2D [30]. Hou et al (2021) reported a statistically significant decrease in the SOD activity in participants with T2D when compared with that in healthy individuals [5]. Similarly, Lipa et al (2016) concluded that low serum levels of SOD significantly correlated with the increased risk of T2D and cataract development among individuals with T2D [31].…”
Section: Discussionsupporting
confidence: 89%
“…Oxidative stress (OS) might be one of the major risk factors of early-onset T2D and the development of diabetic complications [3,4]. OS is associated with increased reactive oxygen species (ROS) production and decreased efficiency in antioxidant systems [5]. T2D is reportedly significantly related to OS, and persistent long-term hyperglycemia can lead to excessive ROS formation in patients with diabetes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our results were agreed with the findings reported by (Bokhary et al, 2021) SOD levels were found to be significantly lower in diabetic participants than in nondiabetic controls. Additionally, (Hou et al, 2021) demonstrated that SOD activity was shown to be lowest in diabetic patients with complications; this automatically increased the amount of lipid peroxides (malondialdehyde), as compared to individuals who were not diagnosed with MVC complications or those in the control group.…”
Section: Relation Of Serum Sod With Diabetic Retinopathymentioning
confidence: 99%
“…Another research demonstrated that Compared to controls, superoxide dismutase levels were drastically reduced in cases, although malondialdehyde levels were dramatically elevated (Chatterjee & Chakraborti, 2020) . Additionally, (Hou et al, 2021) demonstrated that SOD activity was shown to be lowest in diabetic patients with complications; this automatically increased the amount of lipid peroxides (malondialdehyde), as compared to individuals who were not diagnosed with MVC complications or those in the control group.…”
Section: Correlation Mda With Sod Gsh and Zinc In Diabetic Patients W...mentioning
confidence: 99%
“…Additionally, a recent study reported that MDA levels were significant increase in patients with complications and without complications as compared to their heathy counterparts along with a significant reduction in SOD activity in T2D patients [ 75 ]. In agreement, others have shown that MDA levels were significantly elevated in patients with T2D, and this effect was more pronounced in those with microvascular complications when compared to healthy control subjects [ 47 , 76 ].…”
Section: Lipid Peroxidation In Type 2 Diabetesmentioning
confidence: 99%